What can research on indirect translation do for Translation Studies? - Pieta Hanna; Ivaska Laura; Gambier Yves (JOHN BENJAMINS PUBLISHING CO, 2022)
This special issue is about indirect translation (ITr). To counter the traditional disinterest of Translation Studies in researching ITr, it explores and showcases what research on the topic can do for our discipline as a whole. This introductory article prepares the ground for and provides an overview of what is discussed in the seven articles included in the special issue. Before introducing the contributions to this issue, we briefly explain the terminology and definitions used throughout this issue. In the spirit of transparency, and making this special issue useful to everyone in Translation Studies, this introduction also devotes space to discussing how this issue came into being, sharing some of the lessons learnt through guest editing.